(untitled) (Studia theodisca, 2011)
The so-called Rönne-complex belongs to Benn’s early prose production and consists of a cycle of short texts held together by the anti-hero Rönne. Although he presents features which might suggest an identification with his author, the main character is not to be reduced to a mere mask or to Benn’s alter ego. Rönne represents only a partial autobiographical projection of his author, as he is exclusively concerned with the problem of art and expression. According to Nietzsche, he can only justify the world as a work of art.